Generation of Murine Bone Marrow and Fetal Liver Chimeras. Issue 4 (9th April 2021) - Chappaz, Stéphane; Saunders, Tahnee L.; Kile, Benjamin T.
Abstract: The generation of radiation chimeras allows researchers to substitute the hematopoietic system of a mouse with that of one or more donors. A suspension of hematopoietic stem cells (HSCs) is prepared from the bone marrow (BM) or the fetal liver (FL) of a donor mouse and adoptively transferred into an irradiated recipient. Within days, the donor's HSCs will engraft, and their progeny will quickly replace the blood cells of the recipient. This simple tool, together with the large availability of genetically modified mouse lines, can be harnessed to manipulate and study various aspects of blood cell biology in vivo. We present here protocols to generate three types of radiation chimera: (1) BM chimeras, which can assist in determining whether the origin of a genetically based phenotype is the hematopoietic or radio‐resistant compartment and which are also conducive for studying the ecology of blood cells and for manipulating the environment hematopoietic cells live; (2) FL chimeras, which allow the study of hematopoietic systems from animals that carry genetic modifications incompatible with postnatal life; and (3) mixed BM chimeras, in which the hematopoietic system comprises blood cells of two different genotypes. Mixed BM chimeras can be used to identify genes that affect hematopoietic cell fitness and to establish whether secreted factors mediate a phenotype of interest. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Generation of bone marrow chimera Basic Protocol 2 : Generation of fetal liver chimera Basic Protocol 3 : Generation of mixed bone marrow chimera Support Protocol 1 : Isolation of bone marrow cells Support Protocol 2 : Cell counting by flow cytometry Support Protocol 3 : Assessment of chimerism